2024
DOI: 10.3389/fphar.2024.1343587
|View full text |Cite
|
Sign up to set email alerts
|

Evolving role of semaglutide in NAFLD: in combination, weekly and oral administration

Evgenia Koureta,
Evangelos Cholongitas

Abstract: Non alcoholic fatty disease (NAFLD) is the most common chronic liver disease that is managed in the liver departments. It seems that the prevalence of the disease is rising worldwide and as it has the same pathogenetic pathways with metabolic syndrome, treatments that target components of the metabolic syndrome seem promising for the therapy of NAFLD as well. In this review we discuss the evolving role of semaglutide, which is a glucagon-like peptide-1 receptor agonist (GLP-1 RA) that has been already approved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A viable therapeutic option for the treatment of MAFLD is the antidiabetic drug semaglutide, which is available on the market either as a subcutaneous injection or as an oral drug [55]. Semaglutide is an agonist of the GLP-1 receptor which, when binding to the GLP-1 receptor, triggers various signaling mechanisms that lead to insulin secretion and a reduction in glucagon, which in turn results in a reduction in blood glucose levels [56]. This drug is also approved for the treatment of obesity, as it can promote weight loss by regulating appetite and inhibiting gastric emptying [56,57].…”
Section: Incretin and Glucagon Receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…A viable therapeutic option for the treatment of MAFLD is the antidiabetic drug semaglutide, which is available on the market either as a subcutaneous injection or as an oral drug [55]. Semaglutide is an agonist of the GLP-1 receptor which, when binding to the GLP-1 receptor, triggers various signaling mechanisms that lead to insulin secretion and a reduction in glucagon, which in turn results in a reduction in blood glucose levels [56]. This drug is also approved for the treatment of obesity, as it can promote weight loss by regulating appetite and inhibiting gastric emptying [56,57].…”
Section: Incretin and Glucagon Receptor Agonistsmentioning
confidence: 99%
“…Semaglutide is an agonist of the GLP-1 receptor which, when binding to the GLP-1 receptor, triggers various signaling mechanisms that lead to insulin secretion and a reduction in glucagon, which in turn results in a reduction in blood glucose levels [56]. This drug is also approved for the treatment of obesity, as it can promote weight loss by regulating appetite and inhibiting gastric emptying [56,57]. Last year, a meta-analysis by Zhu et al reported that semaglutide significantly reduced hepatic steatosis, inflammation, hepatocellular ballooning and liver stiffness, while the effect on reducing fibrosis stage is still uncertain [58].…”
Section: Incretin and Glucagon Receptor Agonistsmentioning
confidence: 99%